Broken arrow [videorecording (DVD)] - Stewart, James, 1908-1997; Chandler, Jeff, 1918-1961; Paget, Debra, 1933-; Hubert, Rene, 1895-1976; Arnold, Elliott, 1912-1980 (Twentieth Century Fox Home Entertainment, 2007)
Tom believes the Apaches are treated unfairly. After befriending their leader Cochise and arranging a truce, he is called upon by an Army General to negotiate a government peace treaty, but later is the target of a renegade ambush.